2013
DOI: 10.7175/fe.v14i4.658
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dose rounding of cancer therapy on cost avoidance: a pilot study

Abstract: BACKGROUND: A significant and progressive cost rising in medical oncology due to the incorporation of novel and highly expensive drugs into clinical practice have been seen in the past ten years. Dose rounding is an option might be used in oncology settings to avoid extra cost. The purpose of this project is to determine the theoretical cost saving related to a dose rounding process for biological and chemotherapy agents in adult oncology settings and to determine the opinion of oncologists about dose rounding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 13 publications
0
12
0
1
Order By: Relevance
“…11,[32][33][34] However, dose rounding for high cost cytotoxic drugs especially targeted therapies such as monoclonal antibody cytotoxic drugs is not commonly adopted despite the fact that up to 45% of the cost of these biologic cytotoxic drugs could be saved by rounding dose according to the nearest standard vial size (as long as the dose was within 10% of calculated dose). 6,33,35 Therefore, the practice of dose rounding of cytotoxic drug according to standard vial size could be employed by Oncology Pharmacy to reduce the expenditure on cytotoxic drug while providing quality cancer treatment.…”
Section: Rising Global Cancer Burden -Existing and Potential Strategimentioning
confidence: 99%
“…11,[32][33][34] However, dose rounding for high cost cytotoxic drugs especially targeted therapies such as monoclonal antibody cytotoxic drugs is not commonly adopted despite the fact that up to 45% of the cost of these biologic cytotoxic drugs could be saved by rounding dose according to the nearest standard vial size (as long as the dose was within 10% of calculated dose). 6,33,35 Therefore, the practice of dose rounding of cytotoxic drug according to standard vial size could be employed by Oncology Pharmacy to reduce the expenditure on cytotoxic drug while providing quality cancer treatment.…”
Section: Rising Global Cancer Burden -Existing and Potential Strategimentioning
confidence: 99%
“…1 A substantial proportion of these expenditures stems from the incorporation of these expensive novel oncology drugs into clinical practice. 2 One method of containing costs in adult oncology is the utilization of dose rounding cytotoxic chemotherapy and biologic agent doses to the nearest vial size. 2,3…”
Section: Introductionmentioning
confidence: 99%
“…Most dose-rounding protocols address traditional chemotherapy and support rounding within 5% to 10% of the ordered dose. 2,3 This practice is based on variances within dose calculations, pharmacokinetic principles, and clinical evidence. Traditional chemotherapy doses are most often calculated using body surface area (BSA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brenda et al 5 found that dose rounding could reduce drug wastage for up to 42% and resulted in a potential cost savings of $24,434 for 3-month interval. In another study done by Nagwa Ibrahim, 7 dose rounding of anti-cancer agents may save around $192,800 per year. Our study reveals that the projected annual saving was calculated to be SR 176,651.40 for 5% rounding limit and SR 637,890.00 for 10% rounding which will account to an estimate of SR 814,514.40 ($217,204) of drug wastage per year.…”
mentioning
confidence: 99%